Women and Others
XVII, 205 p.
Keywords: Discussing intersecting discourses of race, gender and empire in literature, history and contemporary culture, the book begins with the metaphor of 'the other woman' as a repository for the 'otherness' of all women in a masculinist-racist society and shows how discourses of race and sexuality thwart the realization of true inter-racial sisterhood.